A controversial investment: An industrial policy analysis of the Intel-Magdeburg subsidy based on the BESTInvest guidelines - Nils Gerresheim; Max Krahé (Dezernat Zukunft e.V., 2024)
The US semiconductor company Intel is planning to build two ultra-modern chip factories near Magdeburg. This project was promised the largest industrial policy subsidy that the German government has ever approved for an individual company: almost 10 billion euros. Is this money well-spent? To answer this question, we developed guidelines for the evaluation of government investments (BESTInvest). This paper sets out these guidelines and applies them to Intel-Magdeburg. Our conclusion is that the subsidy is controversial. Although learning curve-, cluster- and innovation effects can create path dependencies in semiconductor production, there are uncertainties surrounding the size of these effects, and the impact of a single subsidy is likely to be moderate. Accordingly, it remains unclear whether the support would suffice to make Intel-Magdeburg competitive in the long term. In addition, relatively few jobs would be created, in a local labour market where there is currently a shortage of skilled workers. This calls into question the effects of the project on the regional and wider economy. In addition to economic factors, there are also relevant climate and sovereignty factors, which are positive but moderate. The over-all assessment therefore depends on the respective weights given to individual factors, as well as, if necessary, on the willingness to promote cluster formation and the competitiveness of the semiconductor industry in Germany and Magdeburg with further measures.
Keywords: 330; intel-magdeburg; semiconductors; industrialpolicy